Homework and academic achievement in Primary Education - Valle, Antonio (2015)
This paper analyzes the relationship between homework behavior and academic achievement using a sample of students from the last three years of primary education. The variables associated with student involvement in homework were the amount of homework completed, the time spent on homework, and homework time optimization, while academic achievement was estimated based on the grades in mathematics and foreign language (english). The possible effect of the course and gender when calculating the level of predictive variables concerning the homework on academic achievement was analyzed. The results indicated that the amount of homework done and the optimization of the time dedicated at homework significantly and positively predicted academic performance in both subjects. However, the amount of time spent on homework was not relevant. Finally, while gender was not statistically significant in predicting academic achievement, the course itself was statistically significant: as the course advances the mathematics achievement tends to diminish.